Purpose, potential and realization of chip-attached micro-pin fin heat sinks. Issue 9 (August 2015) - Conrad, M.; Diatlov, A.; De Doncker, R.W.
Abstract: This work presents the design process of an actively cooled power semiconductor package that makes use of a structured chip contact that is preferably produced by Selective Laser Melting (SLM). The concept has a drastically reduced amount of material transitions within the cooling path and is designed for low thermo-mechanical stress. It is shown how to design and build the geometry of the integrated heat sink in such a way that plastic deformation of the applied materials is kept as low as possible. The comparison with state-of-the-art actively cooled power modules shows that a similar or even smaller thermal resistance can be achieved in a much smaller volume. Highlights: Actively cooled power semiconductor package that makes use of the Selective Laser Melting (SLM) Designed for low thermo-mechanical stress Measurements of the area related thermal resistance are presented to illustrate the performance of the concept.